Pancreatic cancer causing acute pancreatitis: a comparative study with cancer patients without pancreatitis and pancreatitis patients without cancer. Issue 6 (August 2013) - Minato, Yohei; Kamisawa, Terumi; Tabata, Taku; Hara, Seiichi; Kuruma, Sawako; Chiba, Kazuro; Kuwata, Go; Fujiwara, Takashi; Egashira, Hideto; Koizumi, Koichi; Saito, Itaru; Endo, Yuka; et al.
Abstract Background/purpose Although pancreatic cancer produces upstream obstructive pancreatitis, acute pancreatitis is a less common manifestation of pancreatic cancer. This study aimed to clarify the subgroup of pancreatic cancer patients who present with an episode of acute pancreatitis (Group I) in comparison with a matched group of pancreatic cancer patients without pancreatitis (Group II) and another group of acute pancreatitis patients without pancreatic cancer (Group III). Methods This was a retrospective comparative study of 18 patients in Group I, 300 patients in Group II and 141 patients in Group III. Results The mean age of Group I was 63.7 years and the male to female ration was 1:0.3. Serum CA 19–9 levels were elevated in 80 %. The main pancreatic duct was incompletely obstructed in 7 patients. There were no significant differences in location of tumor, clinical stage, resection rate and survival months between Group I and II. Acute pancreatitis secondary to pancreatic cancer was more likely to be mild (94 vs. 72 %, p < 0.05) and relapsed (39 vs. 16 %, p < 0.05) compared with Group III. Conclusions Anatomic evaluation of the pancreas should be performed in patients with acute pancreatitis with no obvious etiology, even if the pancreatitis is mild, to search for underlying malignancy.